Henoch-Schönlein Purpura: Management and Complication - Radhitya Farizky Deta Juniawan; Awalia Awalia (Biomolecular and Health Science Journal, 2020)
Henoch-Schönlein Purpura (HSP) is a disease that mainly affects children, while the incidence in adults is rarely reported. Low incidence in adults caused by undiagnosed or misdiagnosed. Course of the disease in adults is more complex, including high incidence of renal insufficiency. Renal manifestations need special attention because it can worsen the prognosis, so patients must be detected and treated as quickly as possible. Poor prognosis depends on the presence of renal clinical manifestations accompanied by an increase in the severity of renal histological grading, abdominal manifestations, and persistent purpura. We describe male patients with HSP, presenting with gastrointestinal, renal, and cutaneous manifestations. Gastroscopy showed superficial gastritis (reddish patches on almost all gastric mucosa. Skin biopsy showed lymphocytic vasculitis. Gastric biopsy shows infiltration of lymphocyte inflammation cells, histiocytes, plasma cells in the corpus and gastric antrum. Patients have received supportive therapy, steroid, and showed clinical improvement.